2020
DOI: 10.7759/cureus.9021
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hands-On Versus Online Learning in Teaching Ultrasound Skills for Achilles Tendon Rupture: A Pilot Study

Abstract: In the emergency department, the diagnosis of an Achilles tendon rupture (ATR) is reportedly missed in greater than 20% of cases. A limited number of studies evaluate the use of cadaver models as a potential ultrasound teaching and training modality. We hypothesize that emergency medicine residents can effectively utilize point-of-care ultrasound (POCUS) on cadaver models and a focused teaching intervention to assess their ability to detect ATRs. Methods A prospective study of 23 EM residents was performed. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A previous study showed that there was no difference between web-based learning and face-to-face education in the acquisition of knowledge in EFAST use [27]. In addition, other studies demonstrated that online learning showed non-inferiority in terms of skill acquisition in cardiac and musculoskeletal US [28,29]. Thus, online education can be a viable alternative to traditional face-to-face learning in pediatric POCUS training.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that there was no difference between web-based learning and face-to-face education in the acquisition of knowledge in EFAST use [27]. In addition, other studies demonstrated that online learning showed non-inferiority in terms of skill acquisition in cardiac and musculoskeletal US [28,29]. Thus, online education can be a viable alternative to traditional face-to-face learning in pediatric POCUS training.…”
Section: Discussionmentioning
confidence: 99%
“…Another study demonstrated the non-inferiority of web-based learning to face-to-face education in knowledge acquisition of EFAST [ 15 ]. In addition, other studies demonstrated that online learning was non-inferior in terms of skill acquisition in the cardiac and musculoskeletal US [ 16 , 17 ]. A comparative study demonstrated no significant differences in knowledge acquisition between hybrid and traditional in-person POCUS training courses [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this situation, most lectures and conferences have moved online or have combined face-to-face teaching with online tutorials [14]. Some studies have demonstrated the effectiveness of this teaching method [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…EM physicians have previously identified barriers to CUS utilization, including a lack of confidence and comfort in operating the machine, obtaining images, interpreting images within the core modalities, and documentation of examinations [17][18][19][20]. While there are examples of train-the-trainer, ultrasound workshops in critical care settings, targeted organ pathology, and simulation cases, there is a paucity of CUS educational approaches that specifically address these barriers and target the needs of non-certified practicing EM physicians [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%